1999
DOI: 10.1093/emboj/18.15.4332
|View full text |Cite
|
Sign up to set email alerts
|

Dbp5, a DEAD-box protein required for mRNA export, is recruited to the cytoplasmic fibrils of nuclear pore complex via a conserved interaction with CAN/Nup159p

Abstract: contributed equally to this work Dbp5 is a DEAD-box protein essential for mRNA export from the nucleus in yeast. Here we report the isolation of a cDNA encoding human Dbp5 (hDbp5) which is 46% identical to yDbp5p. Like its yeast homologue, hDbp5 is localized within the cytoplasm and at the nuclear rim. By immunoelectron microscopy, the nuclear envelope-bound fraction of Dbp5 has been localized to the cytoplasmic fibrils of the nuclear pore complex (NPC). Consistent with this localization, we show that both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
266
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(290 citation statements)
references
References 69 publications
20
266
0
4
Order By: Relevance
“…With this single-base pair addition, the GRTH cDNA contains 357 additional base pair and an ATG codon (ϩ1) 5Ј in-frame to the original cDNA ATG codon (earlier defined as ϩ1 bp, now revised as ϩ343 bp). This sequence of 1630 bp contains an open reading frame encoding 483 amino acids, with the additional 114 amino acids resulting from 5Ј sequences of our earlier reported clone ( N-terminal sequences are conserved between GRTH of rat, mouse, and human and DBP5 of mouse and human (8,9). Furthermore, our recent studies demonstrated that the TATA-less GRTH gene contains multiple transcriptional start sites located within 80 bp 5Ј to the first ATG codon (ϩ1).…”
Section: Resultsmentioning
confidence: 95%
“…With this single-base pair addition, the GRTH cDNA contains 357 additional base pair and an ATG codon (ϩ1) 5Ј in-frame to the original cDNA ATG codon (earlier defined as ϩ1 bp, now revised as ϩ343 bp). This sequence of 1630 bp contains an open reading frame encoding 483 amino acids, with the additional 114 amino acids resulting from 5Ј sequences of our earlier reported clone ( N-terminal sequences are conserved between GRTH of rat, mouse, and human and DBP5 of mouse and human (8,9). Furthermore, our recent studies demonstrated that the TATA-less GRTH gene contains multiple transcriptional start sites located within 80 bp 5Ј to the first ATG codon (ϩ1).…”
Section: Resultsmentioning
confidence: 95%
“…Also, 60 S export was rescued by Nup214 versions that cannot bind Dbp5. Dbp5 interaction with Nup214-Nup159 is required for mRNA export (63,64), suggesting that the observed 60 S export defects are not primarily caused by general inhibition of mRNA export.…”
Section: Discussionmentioning
confidence: 98%
“…Dbp5 predominantly localizes to the cytoplasm and is particularly concentrated at the rim of nuclear pores, where it associates with cytoplasmic fibrils of the nuclear pore complex 116 . This localization requires the nucleo porin protein Nup159 (NUP214 in mammal s) 117,118 .…”
Section: Nuclear Specklesmentioning
confidence: 99%